1986
DOI: 10.1111/j.1365-2265.1986.tb00754.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Oral Contraceptives on Serum Prolactin: A Longitudinal Study in 126 Normal Premenopausal Women

Abstract: A prospective longitudinal study was carried out in 126 normal premenopausal women aged 18-34 years to determine the effect of oral contraceptives containing less than 50 micrograms of oestrogen on serum prolactin concentration. The mean prolactin concentration in patients receiving oral contraceptives (n = 80) rose from a control level of 8.9 ng/ml to 10.2 ng/ml at 3 months (P less than 0.05) and 10.9 ng/ml at 12 months (P less than 0.001). In a parallel group of patients (n = 46) who used intrauterine device… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

1990
1990
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…We assume that the reduction of ovarian mass, which had caused the decrease in estrogen and progesterone levels, was a trigger for the appearance of galactorrhea as in the case of normal postpartum galactorrhea or after the discontinuation of oral contraceptives (21). Later, gallactorrhea persisted, probably due to the mass effect of the adenoma, although supranormal serum estradiol level may have also been the reason for the elevated PRL (4).…”
Section: Discussionmentioning
confidence: 99%
“…We assume that the reduction of ovarian mass, which had caused the decrease in estrogen and progesterone levels, was a trigger for the appearance of galactorrhea as in the case of normal postpartum galactorrhea or after the discontinuation of oral contraceptives (21). Later, gallactorrhea persisted, probably due to the mass effect of the adenoma, although supranormal serum estradiol level may have also been the reason for the elevated PRL (4).…”
Section: Discussionmentioning
confidence: 99%
“…Whether the estrogens in oral contraceptives or hormone replacement therapy are sufficient to cause hyperprolactinemia is controversial. Some studies have shown that estrogen-containing oral contraceptives can indeed cause hyperprolactinemia in percentages ranging from 12 to 30% of treated women, with little influence of the dose of estrogen [105,106] but others have shown either a minimal or no increase in PRL levels [107][108][109][110][111]. On the other hand most studies have shown either no [112][113][114][115] or minimal effect [116] on PRL levels of estrogen replacement therapy following oophorectomy or at menopause with varying doses of estrogens up to 1.25 mg of conjugated estrogens or 50 lg of estradiol daily.…”
Section: Estrogensmentioning
confidence: 99%
“…Some studies have shown that estrogen-containing oral contraceptives can cause hyperprolactinemia in percentages ranging from 12 to 30% of treated women, with little influence of the dose of estrogen [35,36] but others have shown either a minimal or no increase in PRL levels [37][38][39][40][41]. On the other hand most studies have shown either no [42][43][44][45] or minimal effect [46] on PRL levels of estrogen replacement therapy following oophorectomy or at menopause with varying doses of estrogens up to 1.25 mg of conjugated estrogens or 50 µg of estradiol daily.…”
Section: Late Development Of Dopamine Agonist Resistancementioning
confidence: 99%